Flavonoids in mitigating the adverse effects of canine endotoxemia - Móritz, Alma V.; Kovács, Hédi; Jerzsele, Ákos; Psáder, Roland; Farkas, Orsolya (Frontiers in Veterinary Science, 2024)
In dogs, chronic enteropathies, and impaired gut integrity, as well as microbiome imbalances, are a major problem. These conditions may represent a continuous low endotoxin load, which may result in the development of diseases that are attributable to chronic inflammation. Flavonoids are polyphenolic plant compounds with numerous beneficial properties such as antioxidant, antiinflammatory and antimicrobial effects. For our experiments, we isolated primary white blood cells (peripheral blood mononuclear cells and polymorphonuclear leukocytes) from healthy dogs and induced inflammation and oxidative stress with Escherichia coli and Salmonella enterica serovar Enteritidis lipopolysaccharide (LPS). In parallel, we treated the cell cultures with various flavonoids luteolin, quercetin and grape seed extract oligomeric proanthocyanidins (GSOP) alone and also in combination with LPS treatments. Then, changes in viability, reactive oxygen species (ROS) and tumor necrosis factor alpha (TNF-α) levels were measured in response to treatment with quercetin, luteolin and GSOP at 25 and 50 µg/ml concentrations. We found that ROS levels were significantly lower in groups which were treated by flavonoid and LPS at the same time compared to LPS-treated groups, whereas TNF-α levels were significantly reduced only by luteolin and quercetin treatment. In contrast, treatment with lower concentrations of GSOP caused an increase in TNF-α levels, while higher concentrations caused a significant decrease. These results suggest that the use of quercetin, luteolin and GSOP may be helpful in the management of chronic intestinal diseases in dogs with reduced intestinal barrier integrity or altered microbiome composition, or in the mitigation of chronic inflammatory processes maintained by endotoxemia. Further in vitro and in vivo studies are needed before clinical use.